Outness predicts greater leukocyte telomere length in sexually minoritized men with HIV who use methamphetamine - Renessa S. Williams; Ariana Johnson; Michael Miller-Perusse; Annesa Flentje; Judy Moskowitz; Samantha E. Dilworth; Keith J. Horvath; Adam W. Carrico; Brad E. Aouizerat; Delaram Ghanooni (Brain, Behavior, & Immunity - Health)
Objective: This longitudinal study aimed to examine the associations of sexual minority stress and outness with leukocyte telomere length across time among sexually minority men (SMM) with HIV who use methamphetamine. Methods: A sample of 91 SMM with HIV with biologically confirmed recent methamphetamine use completed measures of sexual minority stress and outness at the baseline visit in a randomized controlled trial. Telomere length was measured over 15 months using extracted leukocyte DNA Statistical analyses were performed using bivariate analyses and generalized estimation equations to examine the independent association between baseline outness and leukocyte telomere length, adjusting for chronological age and recent stimulant use. Results: Greater outness was significantly associated with longer telomere length (estimate = 0.008; CI: 0.001–0.008) after adjusting for chronological age and stimulant use. There was no evidence that stimulant use, intervention assignment, or race/ethnicity moderated the association between outness and greater leukocyte-telomere length. Sexual minority stress was not significantly associated with leukocyte-telomere length. Conclusion: Findings are among the first to demonstrate that greater outness is associated with slower biological aging in SMM. Further research is needed to elucidate the bio-behavioral mechanisms linking outness and greater leukocyte-telomere length.